2018
DOI: 10.1007/s13346-018-0571-z
|View full text |Cite
|
Sign up to set email alerts
|

Cationic cholesterol derivative efficiently delivers the genes: in silico and in vitro studies

Abstract: The aims of the research work were to synthesize ethyl(cholesteryl carbamoyl)-L-arginate (ECCA), an arginine-conjugated cholesterol derivative, and to evaluate its application as a gene delivery vector. The interactions of ECCA with DNA duplex were studied using molecular dynamics (MD) simulations. It was found that the guanidine group of ECCA could interact with the phosphate group of DNA through ionic interactions as well as hydrogen bonds. The structure of DNA was stable throughout the simulation time. Lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Cationic liposomes (CLs) are near-spherical vesicles with a positive charge and are dominantly composed of cationic lipids that effectively condense nucleic acids 1 , 2 , 3 , 4 such as plasmid DNA (pDNA), messenger RNA (mRNA), or small interfering RNA (siRNA) via electrostatic interactions 5 to form complexes called “lipoplexes.” Based on the fact that genes have been revealed to be involved in the development of cancer, 6 , 7 CLs have been extensively studied in cancer gene therapy and have shown potential clinical success in different tumors ( Table 1 ). In general, the selection of CLs as gene carriers is attributed to their permanent positive charge, which promotes their stronger interaction with negatively charged substances such as nucleic acid, cell membrane, and endosomal membrane.…”
Section: Main Textmentioning
confidence: 99%
“…Cationic liposomes (CLs) are near-spherical vesicles with a positive charge and are dominantly composed of cationic lipids that effectively condense nucleic acids 1 , 2 , 3 , 4 such as plasmid DNA (pDNA), messenger RNA (mRNA), or small interfering RNA (siRNA) via electrostatic interactions 5 to form complexes called “lipoplexes.” Based on the fact that genes have been revealed to be involved in the development of cancer, 6 , 7 CLs have been extensively studied in cancer gene therapy and have shown potential clinical success in different tumors ( Table 1 ). In general, the selection of CLs as gene carriers is attributed to their permanent positive charge, which promotes their stronger interaction with negatively charged substances such as nucleic acid, cell membrane, and endosomal membrane.…”
Section: Main Textmentioning
confidence: 99%
“…It has been already reported that gene delivery systems formed by amino acid-based cationic lipids are internalized by habitual endocytic uptake pathways. Thus, the incorporation of amino acid moieties to the head groups of cationic lipids does not seem to change the cellular uptake mechanism, but it can improve the intracellular delivery [33,[42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…With their positive charge, cationic liposomes, can be used to easily encapsulate plasmid DNA (pDNA), messenger RNA (mRNA), or small interfering RNA (siRNA) via electrostatic interactions [131]. An important example is the T7 peptide modified core-shell nanoparticles (named as T7-LPC/siRNA NPs).…”
Section: Liposomes and Immune-gene Therapymentioning
confidence: 99%